THE INFLUENCE OF E-WOM AND PRICE DISCOUNT ON IMPULSE BUYING AT E-COMMERCE USERS IN PEKANBARU: Case Study Pekanbaru Student - Puspita, Adella; Afwa, Awliya; Moniko, Moniko (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This research aims to evaluate the influence of E-WOM and Price Discount on Impulse Buying among e-commerce users in Pekanbaru, with a focus on students in Pekanbaru. The research sample includes 140 respondents actively engaged in impulsive buying behavior. The data analysis method employed is Structural Equation Modeling (SEM) with the assistance of Smart PLS version 3. The research findings indicate that E-WOM does not have a significant impact on Impulse Buying by e-commerce users in Pekanbaru. However, Price Discount has a positive and significant influence on Impulse Buying among e-commerce users in Pekanbaru. Furthermore, based on the determination test, it can be concluded that concurrently, both E-WOM and Price Discount affect Impulse Buying among e-commerce users in Pekanbaru.